Value-based care as a solution to resolve the open debate on public healthcare outsourcing in Europe: What do the available data say? - Caramés, Cristina; Arcos, Javier; Pfang, Bernadette; Cristóbal, Ion; Álvaro de la Parra, Juan Antonio (Frontiers in Public Health, 2024)
Controversy surrounds the current debate regarding the effects of outsourcing health services, as recent studies claim that increased outsourcing leads to reduced costs at the expense of worse patient outcomes. The goal of the value-based model is to enable healthcare systems to create more value for patients, and evidence points to improvements in public health outcomes, patient experience, and health expenditure in systems incorporating components of value-based healthcare. Some emerging evidence indicates promising results for outsourced hospitals which follow a value-based model of healthcare delivery. Although additional future studies are still needed to confirm these benefits, value-based healthcare merits discussion as a new perspective on the public versus private management debate. In fact, we argue that outsourcing to valuebased health providers could represent a valid alternative for public health management, encouraging greater competition within the healthcare sector while ensuring quality of care for both public and private sectors.